Construction of SnS-Mo-graphene nanosheets composite for highly reversible and stable lithium/sodium storage. (10th September 2022) - Cheng, Deliang; Yang, Lichun; Hu, Renzong; Cui, Jie; Liu, Jiangwen; Zhu, Min
Highlights: We report the simple synthesis of ternary SnS-Mo-GNs composite. The composite has the structure of SnS nanoparticles tightly bonded with Mo and GNs. The Mo and GNs function as dual buffer to suppress the Sn agglomeration during cycling. The composite exhibits superior reversibility and cycleability for Li/Na-storage. Abstract: Sn-based chalcogenides are considered as one of the most promising anode materials for lithium-ion batteries (LIBs) because of their high capacities through both conversion and alloying reactions. However, the realization of full capacities of Sn-based chalcogenides is mainly hindered by the large volume variation and inferior reversibility of conversion reaction during cycling. In present work, a new ternary SnS-Mo-graphene nanosheets (SnS-Mo-GNs) composite is fabricated by a simple and scalable plasma milling method, in which SnS nanoparticles are tightly bonded with Mo and GNs. The Mo and GNs additives can effectively alleviate the large volume change of SnS upon cycling, which leads to a stable electrochemical framework. Moreover, they can significantly suppress the Sn agglomeration in lithiated SnS, which enables highly reversible conversion reaction during cycling. As anode for LIBs, the SnS-Mo-GNs composite exhibits a high initial coulombic efficiency of 86.9% (almost complete reversibility of SnS, ∼97.3%), high cyclic coulombic efficiency after initial three cycles (> 99.5%), and long lifespan (up to 600 cycles). Moreover, it also demonstrates superior electrochemical performance for sodium storage. Thus, this work demonstrates a potential anode for batteries application and provides a viable strategy to obtain highly reversible and stable anodes for lithium/sodium storage. Graphical Abstract: Image, graphical abstract